PRACTICE IN TECHNICAL EDUCATION - ZUKERSTEIN, Jaroslav; NOVOTNÝ, Jan (Trends in education, 2009)
This contribution deals with the project established by Development Fund of Universities called "Clinical School of Technical Spare-Time and Creative Activity". It is a very specific kind of practice which is focused on students of technical education pedagogy and it has run in frame of technical activities realized by Faculty of Production Technology and Management for pupils of basic and high schools called "Spring School of Technics". Students were able to apply pedagogical competencies under supervision of experienced specialists in area of organization and managing spare-time activity. Pupils of basic and high schools were subsequently able to try non-traditional technology. Project was realized as a practice of students in conditions that are unavailable at basic and high schools due to lack of technical materials and also specialized HR. In the contribution there is described essential information about the project, its preparation and realization.
Keywords: practice; technical education; project; school of technics.